Spatio-temporal changes in rural settlements: A case study of the Bošácka dolina valley - Najdený, Roman; Gurňák, Daniel (Geografický časopis / Geographical Journal, 2024)
The purpose of this article is to analyse the transformation of rural settlements, including an approximation of the number of inhabitants, through a detailed analysis of the built-up areas – buildings over a time horizon of approximately 170 years in the The Bošácka dolina valley (White Carpathians, Western Slovakia). The analysis includes a detailed survey of the functional use of the housing stock in a selected part of the studied region. The results proved a growing concentration of settlements in the studied area. At the same time, they confirmed the process of the functional transformation of areas with dispersed settlements, where residential buildings are converted into recreation facilities (cottages) or seasonal dwellings or remain uninhabited. This process exhibits spatial heterogeneity within the studied area, predominantly impacting marginal regions characterized by dispersed settlements. The functional transformation of buildings and depopulation were also confirmed by the data on the number of inhabitants, where a dynamic decrease in the number of inhabitants can be seen, especially in the extravillage areas of the investigated municipalities. The study findings indicate the loss of the original function of the dispersed settlement, which is spatially most evident in marginal areas and indicates the disappearance of dispersed settlements